2000
DOI: 10.1080/00420980020080661
|View full text |Cite
|
Sign up to set email alerts
|

Brownfields Redevelopment, Preferences and Public Involvement: A Case Study of an Ethnically Mixed Neighbourhood

Abstract: A survey was conducted with over 200 residents of a largely Hispanic census tract in the City of Perth Amboy, NJ, in order to identify their preferences for brownfield redevelopment and the extent to which residents want to participate in the redevelopment process. We found that residents preferred recreation, cultural and other community facilities, followed by new housing. They were less interested in industry and business. Three-quarters of respondents indicated a desire to participate in the redevelopment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(54 citation statements)
references
References 20 publications
1
51
0
Order By: Relevance
“…These findings are consistent with surveys of brownfield redevelopment in urban areas that show that residents want recreation and community facilities on remediated sites (Greenberg & Lewis, 2000), even though the original concept behind brownfield redevelopment was to replace lost production jobs with other jobs. Furthermore, contrary to the assertion that no one would want to live on a former brownfield site, a New Jersey survey (Greenberg et al, 2001) found that 14 percent of respondents were both planning to move during the next five years and would be willing to live in housing on top of cleaned-up brownfield sites.…”
Section: Managing the Assets And Plausible End States: Immediate Contsupporting
confidence: 85%
“…These findings are consistent with surveys of brownfield redevelopment in urban areas that show that residents want recreation and community facilities on remediated sites (Greenberg & Lewis, 2000), even though the original concept behind brownfield redevelopment was to replace lost production jobs with other jobs. Furthermore, contrary to the assertion that no one would want to live on a former brownfield site, a New Jersey survey (Greenberg et al, 2001) found that 14 percent of respondents were both planning to move during the next five years and would be willing to live in housing on top of cleaned-up brownfield sites.…”
Section: Managing the Assets And Plausible End States: Immediate Contsupporting
confidence: 85%
“…Their perception of soil contamination (Grasmück and Scholz 2005;Vandermoere 2008), willingness to pay for cleanup (Alberini et al 2007), and preferences towards land redevelopment policies (Greenberg and Lewis 2000;Turvani et al 2006) will be a significant deterrence to bureaucratic complacency. Figure 3 shows the flow of technical information and a decision-making diagram.…”
Section: Challenges Of the Site Management Policies In Chinamentioning
confidence: 99%
“…In disadvantaged neighbourhoods a level of trust between brownfields redevelopment partners and neighbours may not exist and care must be taken to build bridges and provide translation services and process education (Greenberg and Lewis 2000). However, developers are not often willing to undertake such efforts.…”
Section: Socio-economically Disadvantaged Communitiesmentioning
confidence: 99%